Black carbon exposure, socioeconomic and racial/ethnic spatial polarization, and the Index of Concentration at the Extremes (ICE). (July 2015) - Krieger, Nancy; Waterman, Pamela D.; Gryparis, Alexandros; Coull, Brent A.
Abstract: Background: Scant data quantify associations between economic and racial/ethnic spatial polarization and individual's exposure to pollution. Methods: We linked data on the socioeconomic position (SEP) of 1757 urban working class white, black, and Latino adults (age 25–64; Boston, MA: 2003–2004; 2008–2010) to: (1) spatiotemporal model-based estimates of cumulative black carbon exposure at their exact residential address, and (2) their census tract values for the Index of Concentration at the Extremes (ICE) for SEP and race/ethnicity. Results: ICE measures, but not individual- and household-SEP, remained independently associated with black carbon exposure. Conclusions: The ICE may be useful for environmental health research. Highlights: We report novel data on social inequalities in residential black carbon (BC) exposure. We used a new social science metric: Index of Concentrations at the Extremes (ICE). ICE contrasts were for income, education, race/ethnicity, and income+race/ethnicity. Black carbon exposure was inversely associated with the ICE measures. ICE associations were independent of individual-level socioeconomic position.